2009
DOI: 10.1111/j.1447-0756.2008.00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of placenta vascularization in patients with uterine altered artery Doppler flow velocity exams

Abstract: The morphological proof that uterine artery Doppler flow velocity exam alterations are associated with placental vascular alterations demonstrates the importance of this exam during prenatal care, even in the absence of maternal-fetal alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The acute reduction of villous size and perimeter associated with active malaria infection seems unlikely to reflect decreased blood flow in the placenta before delivery (for instance due to the effects of vascular obstruction by sequestered parasites, leukocytes or fibrin deposition) because these processes affect the maternal blood space. Changes in villous vascularity and size in other diseases examined using morphometry developed over a longer period due to poor oxygenation and hypertension, leading to defective stem villous development and hence vascularization of terminal villi [ 16 , 29 , 30 ]. Apart from blood flow, the activity of various growth-promoting hormones, such as insulin-like growth factor or placental growth factor, plays a role in supporting normal placental development [ 31 ], but changes in these growth axes would not explain the acute shrinkage seen in malaria infection.…”
Section: Resultsmentioning
confidence: 99%
“…The acute reduction of villous size and perimeter associated with active malaria infection seems unlikely to reflect decreased blood flow in the placenta before delivery (for instance due to the effects of vascular obstruction by sequestered parasites, leukocytes or fibrin deposition) because these processes affect the maternal blood space. Changes in villous vascularity and size in other diseases examined using morphometry developed over a longer period due to poor oxygenation and hypertension, leading to defective stem villous development and hence vascularization of terminal villi [ 16 , 29 , 30 ]. Apart from blood flow, the activity of various growth-promoting hormones, such as insulin-like growth factor or placental growth factor, plays a role in supporting normal placental development [ 31 ], but changes in these growth axes would not explain the acute shrinkage seen in malaria infection.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed a greater number and width of stem, intermediary, and terminal villi vessels in the placentas of patients with Doppler exam alterations, even without clinically relevant placental pathologies. 39 Additionally, automated image analysis systems have been developed for the evaluation of villous morphology in recurrent miscarriage, 40 delayed or accelerated villous maturation, 41 and distal villous hypoplasia (DVH), achieving respectable and reproducible results. In 2016, fractal dimension (a mathematical calculation of image complexity) was compared to the inter-observer agreement among 5 pathologists regarding DVH, a hallmark of IUGR, demonstrating that artificial intelligence has the potential to increase objectivity in reporting a clinically useful lesion.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a greater number and width of stem, intermediary, and terminal villi vessels in the placentas of patients with Doppler exam alterations, even without clinically relevant placental pathologies. 39 Additionally, automated image analysis systems have been developed for the evaluation of villous morphology in recurrent miscarriage, 40 delayed or accelerated villous maturation, 41 and distal villous hypoplasia (DVH), achieving Some papers and abstracts focused on more than one topic and methodic.…”
Section: Machine and Deep Learning Algorithmsmentioning
confidence: 99%
“…During the second trimester fetal screening, the placenta, and the associated anatomical structures are evaluated, and uterine artery Doppler is performed for the prediction of prenatal complications. Previously, studies were conducted to evaluate the relationship between the placental structure during pregnancy or the postnatal period and Doppler parameters (3,4). Population studies have aimed to determine the average placental thickness (PT) during specific periods of pregnancy (2,5,6).…”
mentioning
confidence: 99%